Spectrophotometric Determination of Cefixime Following Simple Diazotization and Coupling with ?-Naphthol - Samar A. Darweesh (College of Pharmacy University of Baghdad, 2017)
Cefixime (CFX) was treated with sodium nitrite and hydrochloric acid for diazotization reaction followed by coupling with ?-Naphthol in alkaline medium to form, a yellow colored azo dye compound which exhibits maximum absorption (?max) at 412 nm where the concentration of (CFX) was determined spectrophotometrically. The optimum reaction conditions and other analytical parameters were evaluated. Beer's law was obeyed in the concentration range of (1-20) ?g.mL-1 with a molar absorptivity of 34870.5 L.mol-1.cm-1. The limit of detection was found to be 0.1090 ?g.mL-1 and the Sandell's sensitivity value was 0.0130 ?g.cm-2. The proposed method could be successfully applied to the determination of (CFX) in pharmaceutical formulations.